Strategic Planning-A New Tool for Creative Management of Institutes - Naik, B. M. (Journal of Engineering Education Transformations, 1994)
With the adoption of privatization policy in engineering education, in India and abroad, a new class of people. "Educational Entrepreneurs" has emerged. They have initiated vigourously critical examination of old values, institutions, missions, work methods., needs of education etc. demanding change in the perceptions of people. They wish to outwit in local and global competition and to make most of the opportunities. They have generated a much needed competitive environment for themselves as well as for Govt. and aided institutes. Institutions now have developed a strong will to win. But mere will and enthusiasm is not enough. They ought to have the skills of strategic planning, without which, they will not be able to stand in competition. The article, therefore prescribes, the adoption of strategic planning, with cut any loss of time, for all institutions including those which are managed and maintained by Government. This is not now an option but a compulsion without which they will become dis functional. The paper presents, in brief, what is meant by strategic planning, what is a mission statement, how to arrive at it, who are stakeholders, how to assess their expectations, how to prepare strategic plan and how to implement it. Forces which Hi-JACK the planning process are identified. Strategies which have worked well in India and abroad, are also presented.